IMPACT OF CLAIMS SETTLEMENT ON PROFITABILITY OF GENERAL INSURANCE COMPANIES IN NIGERIA: A STUDY OF SELECTED LISTED GENERAL INSURANCE COMPANIES - Safiu, Ismaila; Shomuyiwa, Abibat (Journal of Economic Development, Environment and People, 2024)
This study investigates the impact of claims settlement practices on the profitability of general insurance companies in Nigeria. The study employed an ex post facto research design with the use of twenty (20) years’ financial data from 2003 to 2022 from published annual financial reports of five (5) sampled listed non-life insurance companies carrying on insurance business in Nigeria. Hypothesizing the dependent and independent variables with the proxies ROA; and LR, ER; CR. Panel data methods were used with other supporting tests using E-views (version 10) data analysis tool. With a balanced data of 100 observation - five cross-sectional data of 20 years period, the results revealed a negative relationship between the proxies (ER, LR and CR) of the independent variable – Claims settlement practices, as they could only explain to a negligible extent, the changes that occurs in the dependent variable. Premised on the findings, it is recommended that general insurance firms settle genuine claims as prompt as possible while the maintain required underwriting standard to avoid problem of adverse selection engendering possibility of ruin.